Bangkala dan Binamu: Suatu Kajian Naskah Lontara’ Dalam Sosial-Politik Jeneponto Kuno - Muhlis - Hadrawi (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2017)
Jeneponto is one of the toponomi of Makassar kingdom, which is located in the coastal area of South Sulawesi, has its own dynamic history. This study aims to explore socio-political phenomenon of Jeneponto local kingdoms, using two main toponimi of local kingdoms of Jeneponto, Bangkala and Binamu, from their establishment, the dynamic of their growth, and their relationship with the outer kingdoms in XVI and XVII centuries, so as to complete the narrative of socio-political history of Makassar. Based on philological approach, the study relies on Lontara’ Patturioloang through five manuscripts, supported by existing literatures as well as oral tradition. At first, Jeneponto noble hegemony is controlled by Bangkala. Then, this switched to Binamu after Makassar War in 1666. As part of Jeneponto kingdom, Bangkala was firstly developed and had royal blood from Kalimporo. In its development, Bangkala then forged political alliances and genealogy with Gowa since the XVI century. As a local kingdom, Binamu had high noble degree which was rooted from Bantaeng, then it made blood connection with Tallo kingdom. However, since the XVII it established political connection with Bone kingdom. The marriage of Binamu and Bangkala nobles with high nobles of Gowa, Tallo, Bantaeng and Bone not only enhanced the degree of nobility and developed a kinship network, but also became a political strategy for piece.